2018
DOI: 10.1002/anie.201802825
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Binding‐Mediated Gelation/Crystallization and Thermosensitive Superchirality

Abstract: Determination of molecular structural parameters of hydrophobic cholesterol-naphthalimide conjugates for water binding capabilities as well as their moisture-sensitive supramolecular self-assembly were revealed. Water binding was a key factor in leading trace water-induced crystallization against gelation in apolar solvent. Ordered water molecules entrapped in self-assembly arrays revealed by crystal structures behave as hydrogen-bonding linkers to facilitate three-dimensional growth into crystals rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…Thus, crystal formation can lead to increased gel fluidity or its complete collapse. Whereas gel–crystal transitions can be induced in some systems by modulating an environmental factor or introducing an external stimulus, most reports describe its spontaneous occurrence over time periods that vary between months and hours. There are also uncommon reports of rapid transitions occurring in transient gels within minutes …”
Section: Introductionmentioning
confidence: 99%
“…Thus, crystal formation can lead to increased gel fluidity or its complete collapse. Whereas gel–crystal transitions can be induced in some systems by modulating an environmental factor or introducing an external stimulus, most reports describe its spontaneous occurrence over time periods that vary between months and hours. There are also uncommon reports of rapid transitions occurring in transient gels within minutes …”
Section: Introductionmentioning
confidence: 99%
“…This result indicated that the water plays important role in the assembly process. The water may supply assembly driving forces based on the solvent effect, hydrogen bonding interactions as well as hydrophobic interactions [15] . The critical gelation concentration (CGC) was found to be 0.3 % in H 2 O: DMF (v: v,3 : 7, 10 mg mL −1 =1 %) or 0.5 % in H 2 O: DMSO (v: v, 2 : 8), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Furthermore,r esponsive gel-to-crystal and gel-to-solution phase transitions can be triggered by various external and internal stimuli, such as light, pH, temperature,ionic strength, and the choice of solvents. [10] Water has very limited solubility in oils like benzene, toluene,a nd trichloromethane. [11] Theh igh surface tension makes water transportation in such media difficult [12] and phase separations will usually occur.…”
Section: Introductionmentioning
confidence: 99%